The Role of Communication and Public Relations in Enhancing Academic Research Promotion - Ioana Julieta JOSAN (Communications of International Proceedings, 2021)
In the last decade, scientific research is facing countless changes, including increasing pressure to ensure better scientific productivity, but also the pressure to digitize its activities. In this context, researchers either become increasingly overwhelmed by these changes or become active agents of change in science. From the first category there is no possibility to develop a successful academic career without adapting to new trends. One of these trends is the promotion of scientific research, but also of the researchers increasing their visibility, recognition, and position in the scientific community. Therefore, the relationship between communication and public relations and scientific communication is becoming closer. Many of the activities required for promotion depend on the ability to use specific knowledge by public relations practitioners. To use these strategies and tactics, researchers need to be aware of their role in increasing their recognition and reputation. The literature review proves a limited attention on this subject and most of them are focused on the impact of social media on scientific results or are institutional guides for promoting online research. From that reason, the aim of the paper is to analyze the use of communication and public relations strategies from another perspective – the individual perspective - members of the academic community (academics, researchers, practitioners) as an integral part of individual and institutional development and recognition.
Keywords: communication; public relations; research promotion; reputation; recognition; scientific productivity